Necessary Factors to Achieve Deep Flexion for Asian Populations after Oxford Unicompartmental Knee Arthroplasty - Inui, Hiroshi; Taketomi, Shuji; Yamagami, Ryota; Kawaguchi, Kohei; Nakazato, Keiu; Tanaka, Sakae (The Journal of Knee Surgery, 2020)
There have been many reports on the clinical outcomes of Oxford unicompartmental knee arthroplasty (UKA); however, none have investigated the influence of flexion angle after UKA on clinical outcomes. The objective of this study was to clarify the relationship between outcomes and the postoperative maximum flexion angle and reveal the necessary factors for maximum flexion angle ≥ 140 degrees which is considered necessary for Asian populations. We categorized 212 UKA patients into the following three groups based on the postoperative maximum flexion angle: group 1 had flexion angle ≥ 140 degrees in 80 patients (38%), group 2 had 130 degrees ≤ flexion angle < 140 degrees in 80 patients (38%), and group 3 had flexion angle < 130 degrees in 52 patients (24%). Furthermore, we compared the postoperative clinical outcomes between the three groups and conducted multivariable regression analyses to assess parameters affecting the flexion angle. Postoperative Knee Society function scores for group 1 was significantly higher than for group 3. Group 1 had higher mean knee injury and osteoarthritis outcome scores (KOOS) in all subscales and significantly higher KOOS scores in the sports and quality of life subscales compared with group 2 and in all subscales compared with group 3. Multivariable logistic regression showed that preoperative flexion angle and tibial component posterior slope were associated with maximum flexion angle ≥ 140 degrees. Maximum flexion angle ≥ 140 degrees after Oxford UKA improved the clinical results, particularly for patient-reported outcomes. Furthermore, the tibial posterior slope was an important factor in achieving maximum flexion angle ≥ 140 degrees in UKA patients.
Keywords: unicompartmental knee arthroplasty; deep flexion; Asian populations; patient-reported outcomes; tibial posterior slope